Technological change and economic catch-up the role of science and multinationals - Santangelo, Grazia D., 1973-; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2005)
This book tackles the issue of technological and economic catch-up by examining the role that public research institutions and local policy play in the promotion of this process by fostering local science-technology linkages with incoming foreign-owned multinationals. Although the book comprises various techno-socio-economic contexts and different methodological perspectives, the authors share the idea that public research, educational and political institutions provide capabilities in basic research and training of highly skilled labour, while private corporations establish networking connections with scientific and professional communities (and therefore access to knowledge and contacts) in other parts of the world.
pt. 1. Local science and technology policy -- pt. 2. International business linkages between foreign-owned multinationals and local actors -- pt. 3. Catch-up and innovative activity in backward areas.
Includes bibliographical references and index.
Keywords: Technological innovations -- Economic aspects -- Developing countries; Science and state -- Developing countries; International business enterprises -- Developing countries; Electronic books